PENGARUH MODEL PROJECT BASED LEARNING BERBANTUAN MEDIA GAMBAR BERSERI TERHADAP KETERAMPILAN MENULIS TEKS PROSEDUR SISWA KELAS VII SMP NEGERI 20 PADANG - Wulandari, Erika; Asri, Yasnur (Universitas Negeri Padang, 2020)
ABSTRACT This purpose of this study is three. First, describing the procedure of writing text for students of class VII in Junior High School 20 Padang before using the project based learning model assisted by the media of serial images. Secondly, describing the procedure of writing text for students of class VII in Junior High School 20 Padang after using the project based learning model assisted by the media of serial images. Third, analyzing the effect of the use of project based learning models assisted by the media of serial images on the skills of writing procedure text for students of class VII in Junior High School 20 Padang. This type of research is quantitative research with one group pretest and posttest design experimental methods. There are three results of this study. First, the procedure of writing text in the seventh grade of Junior High School 20 Padang before using the project based learning model assisted by the media of serial images is of sufficient qualification (C) with an average value of 62,76. Second, the procedure of writing text in the seventh grade of Junior High School 20 Padang after using the project based learning model assisted by the media of serial images is of good qualification (B) with an average grade of 78,52. Third, based on the t-test, H1 is accepted at the 95% confidence level and dk = (n-1) because tcount>ttable (6,25>1,82). Kata Kunci: Pengaruh, Model Project Based Learning, Media Gambar Berseri, Keterampilan Menulis Teks Prosedur